# Integration by Parts

Integration is the calculation of an integral which is used in maths for finding many useful quantities such as areas, volumes, displacement, etc., that occur due to a collection of small data which cannot be measured singularly. Integrals are denoted using ” ∫ “.

The concept of integration is used to solve two types of problems given below :

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the ** Demo Class for First Step to Coding Course, **specifically **designed for students of class 8 to 12. **

The students will get to learn more about the world of programming in these **free classes** which will definitely help them in making a wise career choice in the future.

- When the derivatives are given, find the problem function,
- Find the area which is bounded by the graph of a function under some particular constraints.

These two problems lead to the development of the concept called the **“Integral Calculus”, **which consist of two types of integrals as given below:

**Definite Integral:**An integral that includes the upper and lower limits is known as a definite integral. Definite Integral is also known as Riemann Integral. A definite Integral is represented as:

**Indefinite Integral:**Indefinite integrals do not have upper and lower limits. It is represented as:

∫f(x)dx = F(x) + C

Here C is a constant and f(x) is a function** **that is known as integrand.

There are five types of integration methods available:

- Integration by substitution
- Integration by parts rule
- Integration by partial fraction
- Integration using trigonometric identities
- Integration of some particular function

Here, we only discuss integration by parts.

### Integration by parts

Integration by parts is a method of integration that is often used for integrating the products of two functions. This technique is used to find the integrals by reducing them into standard forms. The following formula is used to perform integration by part:

Where:

u is the first function of x: u(x)

v is the second function of x: v(x)

The formula of integration by parts with limits:

Where:

a is the lower limit

b is the upper limit

**Derivation of Integration By Parts Formula:**

Suppose u and w are any two differentiable functions of a single variable y.

As we already know how to differentiate a product,

y = uwthen, by the product rule of differentiation

dy/dx = d⁄dx(uw) = u d/dx(w) + w d/dx(u)Rearranging this, we get

u d/dx(w) = d⁄dx(uw) – w d/dx(u)

or

uw’ = d⁄dx(wu) – wu’On integrating both sides w.r.t x, we get

∫(uw’)dx = ∫d/dx(uw) dx – ∫(wu’)dxThe first term on the right simplifies, since

we are simply integrating what has been differentiated.

Therefore,

∫(uw’)dx = uw – ∫(u’w) dxNow put

w’ = v

w = ∫vSubstituting the above values, we get

∫(uv)dx = u(∫vdx) – ∫(u’∫vdx)dx

**Rules of integration by parts :**

- Choose the first function as
**u**and the second function as**dv/dx**. - Differentiate u:
**u’** - Integrate dv/dx:
**(∫(dv/dx)dx = v)** - Put u, u’, v and ∫(dv/dx)dx into:
**u(∫vdx) −∫(u’ ∫vdx) dx**

**ILATE Rule**

In Integration by parts, generally, we use the preference order for deciding the first function, using **ILATE **Rule (Inverse trigonometric functions, logarithmic functions, algebraic functions, trigonometric functions, exponential functions). This rule states that the inverse trigonometric function should be assumed as the first function while performing the integration. Hence, the functions are to be assumed in order from **left to right**, by considering the left term (of ILATE) as the first function and the second term (of ILATE) as the second function, depending on the type of function involved. So, ILATE is the order in which we select the first function.

Below are the following steps for function u, where

I= Inverse trigonometric functionssuch as sin

^{-1}(x), cos^{-1 }(x), tan^{-1}(x)

L= Logarithmic functionssuch as ln(x), log(x)

A= Algebraic functionssuch as x

^{2}, x^{3}

T= Trigonometric functionssuch as sin(x), cos(x), tan(x)

E= Exponential functionssuch as e

^{x}, 3^{x}

### Sample Problem

**Question 1. Evaluate ∫2x cos(x)dx**

**Solution: **

Given that, ∫2x cos(x)dx

According to the rule of integration by parts,

Let us consider,

u = 2x and dv/dx = cos(x)

Then

du/dx = 2 and v = ∫cos(x) = sin(x)

Now, using the formula for integration by parts;

∫u(dv/dx)dx = uv – ∫v(du/dx)dx

We get,

∫2x cox(x)dx = 2x sin(x) – ∫sinx.2dx

∫2x cos(x)dx = 2x sin(x) + 2cos(x) + c

where c is a constant.

**Question 2. Evaluate ∫3x ln|x| dx**

**Solution:**

Given, ∫3xln|x| dx

According to rule of integration by parts,

Let us consider,

u = ln|x| and dv/dx = 3x

Then

du/dx = 1/x and v = ∫3xdx = 3x

^{2}/2Now, using the formula for integration by parts,

∫u(dv/dx)dx = uv – ∫v(du/dx)dx

∫3x ln|x|dx = ln|x|.3x

^{2}/2 – ∫3x^{2}/2(1/x)dx= 3x

^{2}/2(ln|x|) – ∫3x/2 dx= 3x

^{2}/2(ln|x|) – 3x^{2}/4 + Cwhere C is a constant.

**Question 3. Evaluate ∫10x ^{2}**

**Solution: **

Given that, ∫10x

^{2}According to rule of integration by parts,

Let us consider,

u = 10x

^{2}and dv/dx = 1Then

du/dx = 20x and v = ∫(1)dx = x

Now, using the formula for integration by parts;

∫u(dv/dx)dx = uv – ∫v(du/dx)dx

∫10x

^{2}dx = 10x^{2}x – ∫x(20x)dx∫10x

^{2}dx = 10x^{3}– ∫20x^{2}dx∫10x

^{2}dx = 10x^{3}– 20/3x^{3}+ C∫10x

^{2}dx = 10x^{3}/3 + Cwhere C is a constant.

**Question 4. Evaluate ∫x ^{2} e^{4x} dx**

**Solution:**

Given that, ∫x

^{2}e^{4x}dxAccording to rule of integration by parts,

Let us consider,

u = x

^{2}and dv/dx = e^{4x}Then

du/dx = 2x and v = ∫e

^{4x }dx = 1/4(e^{4x})Then, using the formula for integration by parts,

∫u(dv/dx)dx = uv – ∫v(du/dx)dx

∫x

^{2}e^{4x }dx = (x^{2})1/4(e^{4x}) – ∫1/4(e^{4x})(2x)dx= 1/4(x

^{2})(e^{4x}) – ∫2/4(x)(e^{4x})dx= 1/4(x

^{2})(e^{4x}) – ∫1/2(x)(e^{4x})dxThe resulting integral is still a product of

two functions i.e. 1/2(x) and e

^{4x}.So, We use the formula for integration again.

This time we take

u = 1/2(x) and dv/dx = e

^{4x}So

du/dx = 1/2 and v = ∫e

^{4x}dx = 1/4(e^{4x})Now, on putting these values in above equation,

∫x

^{2}e^{4x}dx = 1/4(x^{2})(e^{4x}) – ∫2/4(x)(e^{4x})dx= 1/4(x

^{2}e^{4x}) – {2/4(x).1/4(e^{4x}) – ∫(1/4(e^{4x}).2/4 dx}= 1/4(x

^{2}e^{4x}) – 1/8(xe^{3x}) + 1/8(e^{4x}) + Cwhere C is a constant.

**Question 5. Evaluate ∫ 2e ^{x }sin(x) dx**

**Solution:**

Given that, ∫ 2e

^{x}sin(x) dxAccording to rule of integration by parts,

Let us consider,

u = 2e

^{x}and dv/dx = sin(x)Then

du/dx = 2e

^{x}and v = ∫sin(x)dx = -cos(x)Now, using the formula for integration by parts,

∫u(dv/dx)dx = uv – ∫v(du/dx)dx

∫ 2e

^{x}sin(x) dx = (2e^{x})(-cos(x)) – ∫(-cos(x))(2e^{x})dx= -(2e

^{x})cos(x) + ∫ 2e^{x }cos(x)dxThe resulting integral is yet a product of two

functions i.e. 2e

^{x}and cos(x).So, we use the formula for integration again.

This time we take

u = 2e

^{x }and dv/dx = cos(x)So

du/dx = 2e

^{x }and v = ∫cos(x)dx = sin(x)Now, on putting these values in the above equation, we get

∫ 2e

^{x}sin(x) dx = -cos(x)(2e^{x}) + ∫ 2e^{x}cos(x)dx= -(2e

^{x})cos(x) + {2e^{x}sin(x) – ∫sin(x)(2e^{x})dx}= -2e

^{x}cos(x) + 2e^{x}sin(x) – ∫2e^{x}sin(x)dxNow, notice that the integral ∫e

^{x}sin(x)dx in the resultis same as the integral in the given question.

So, let us assume this as I.

Therefore,

I = ∫ 2e

^{x}sin(x) dxSo,

I = 2e

^{x}sin(x) – 2e^{x}cos(x) – I2I = 2e

^{x}sin(x) – 2e^{x}cos(x)2I = 2(e

^{x}sin(x) – e^{x}cos(x))I = (e

^{x}sin(x) – e^{x}cos(x))So,

∫ 2e

^{x}sin(x) dx = e^{x}sin(x) – e^{x}cos(x) + Cwhere C is a constant.

**Question 6. Evaluate ∫2tan ^{-1}x dx **

**Solution:**

Given, ∫2tan

^{-1}x dxAccording to the rule of integration by parts,

Let us consider,

u = tan

^{-1}x and dv/dx = 2Then

du/dx = 1/(1 + x

^{2}) and v = ∫(2)dx = 2xNow, using the formula for integration by parts,

∫u(dv/dx)dx = uv – ∫v(du/dx)dx

∫2tan

^{-1}x dx = tan^{-1}x(2x) – ∫2x(1/(1+x^{2}))dxlet, p = (1 + x

^{2})So, dp/dx = 2x

⇒ x = 1/2

Now, substituting the above values, we get

∫tan

^{-1}x dx = tan^{-1}x(2x) – ∫(1/p)dx= 2xtan

^{-1}x – ∫(1/p)dx= 2xtan

^{-1}x – lnp= 2xtan

^{-1}x – ln(1 + x^{2})= 2xtan

^{-1}x – ln√(1 + x^{2}) + Cwhere C is a constant.